Knowledge of women about breast cancer and self-examination: bibliographical review - Coppo, Cinara Bozolan; Lago, Milena Torres Guilhem (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No 75 (2022): jul./dez., 2022)
Introduction: Cancer is defined as a set of more than 100 diseases that have in common the disordered (malignant) growth of cells that invade tissues and organs, and may spread (metastasize) to other regions of the body (INCA, 2019). Breast cancer is a malignant tumor that develops in the breast tissue. The advantages of performing breast self-examination (BSE) are the detection of small tumors or even confined to the mammary gland, in addition to being a convenient, useful, inexpensive and easy to perform method. The discovery of smaller diameter tumors leads to less mutilating treatment and there is evidence that measures taken in order to reduce clinical staging cause survival benefits and decrease treatment costs. (BRITO et al ., 2010). Objective : The objective of this article is to understand and describe whether women have knowledge about breast cancer and the importance of breast self-examination, and whether they receive any guidance on. Methodology: This is a bibliographic review, which used the following database: google academic, and after applying the inclusion criteria, a sample of 10 articles was obtained. Results: After the 10 analyzed articles that were produced by doctors and nurses who hold degrees as nursing graduates, also as masters and doctors, the selected articles are from the year 2010 to 2019, with all included in the appropriate criterion in the subject, where they were subdivided into two categories. Conclusion: It is concluded that although breast cancer is a major incidence among women today, it is very necessary to implement the approach to the subject on breast cancer and prevention methods and guidelines, such as breast self-examination, as many report that they do not perform because they do not receive information or know about the information, but do not receive guidance on the correct technique. However, it is up to health professionals to exercise an educational role, bringing these women the correct technique, the correct information on breast self-examination, and also as their own self-care.